EU law and private international law the interrelationship in contractual obligations - Kuipers, Jan-Jaap (Nijhoff studies in EU law ;, 2012)
European Union Law and Private International Law both attempt to resolve a conflict of laws. There is however a certain tension between the two disciplines. The present book proposes suggestions to enhance their mutual understanding.